A new Chondrostoma species from the Büyük Menderes River Basin, Turkey (Teleostei: Cyprinidae). Issue 4 (2nd October 2018) - Güçlü, Salim Serkan; Küçük, Fahrettin; Turan, Davut; Çiftçi, Yılmaz; Mutlu, Ayşe Gül
Abstract : In a study of the fishes of the Büyük Menderes River Basin, Aegean region of Turkey, two populations of Chondrostoma were found which showed clearly distinctive characters: the population from the Upper B. Menderes (Işıklı Lake) was attributed to C. meandrense Elvira, 1987, while the population from the Çine Stream in the Lower B. Menderes River basin proved to be a hitherto undescribed species: Chondrostoma turnai sp. n. Altogether 24 metric and 7 meristic parameters were compared. The new species is distinguished from C. meandrense and all other cogeners by a combination of the number of lateral line scales, the number of scale rows between the lateral line and the dorsal-fin origin, the number of scale rows of the lateral line and pelvic-fin origin, and the number of gill rakers on the first gill arch. http://www.zoobank.org/urn:lsid:zoobank.org:pub:811C213D-BEDD-4C8C-AE57-BFFA7964781A